Efficacy and safety of romiplostim in refractory aplastic anaemia: a Phase II/III, multicentre, open‐label study. (5th November 2020) - Jang, Jun Ho; Tomiyama, Yoshiaki; Miyazaki, Koji; Nagafuji, Koji; Usuki, Kensuke; Uoshima, Nobuhiko; Fujisaki, Tomoaki; Kosugi, Hiroshi; Matsumura, Itaru; Sasaki, Ko; Kizaki, Masahiro; Sawa, Masashi; et al.
Abstract: A previous dose‐finding study has suggested that romiplostim is effective in patients with refractory aplastic anaemia (AA) and 10 µg/kg once weekly was recommended as a starting dose. In this Phase II/III, multicentre, open‐label study, romiplostim was administered subcutaneously at a fixed dose of 10 µg/kg once weekly for 4 weeks (weeks 1–4) followed by weekly doses (5, 10, 15 and 20 µg/kg) titrated by platelet response for up to 52 weeks (weeks 5–52). A total of 31 patients with AA who were refractory to immunosuppressive therapy (IST) and thrombocytopenia (platelet count of ≤30 × 10 9 /l) were enrolled. The primary efficacy endpoint of the proportion of patients achieving any haematological (platelet, neutrophil and erythrocyte) response at week 27 was 84% [95% confidence interval (CI) 66–95%]. Trilineage response was 39% (95% CI 22–58%) at week 53. The most common treatment‐related adverse events (AEs) were headache and muscle spasms (each 13%). All AEs were mild or moderate except for three patients with Grade 3 hepatic AEs; no AEs necessitated romiplostim discontinuation. Two patients developed cytogenetic abnormalities, of whom one returned to normal karyotype at last follow‐up. High‐dose romiplostim is effective and well tolerated in the treatment of patients with AA refractory to IST.